Extension of Lotka – Volterra Model as a Means for Economic Policy Adjustment Caused by Conflict - Arakelyan , Aram; Makaryan , Leon (Bulletin of Yerevan University G: Economics, 2022)
Current paper is devoted to the study of the extension of Lotka-Volterra model as a means for the adjustment of countries economic policies acting in the region of their interests. As the model we are considering a system of differential equations. The study of output dynamics based on ordinary differential equation is of great interest in nonlinear systems. The research implemented recently showed a possibility to apply Lotka-Volterra equation in economics, population dynamics, output dynamics, for the estimation of economic cost of the conflict economic. Recently the generalization of the Lotka-Volterra model studied two interactions which captured by the terms presenting outputs.  The equilibrium points and conditions of the stability of Lotka-Volterra model are determined. The general solution of the system of ordinary differential equations is given.Being interested in the study of the application for real world an example of the simulation of Lotka-Volterra model for five countries is given. The cooperative game is considered between acting countries. Through the Shapley vector of the cooperative game the constant coefficients assessing interactions between countries are determined. The effect of countries on the rate of GDP change is analyzing and is comparing with other countries.
Keywords: Lotka-Volterra model; economic policy; adjustment; cooperative game; system of ordinary differential equations; equilibrium; staibility; conflict